Information and communication technologies for development in Africa. - Etta, Florence Ebam; Wamahiu, Sheila P. (Information and communication technologies for development in Africa ;, 2003)
This volume examines the setting, operations, and effects of community telecentres. It describes the telecentre experiences of a variety of local and often rural communities, exploring the management structures and mechanisms that have been established to support these telecentres. The book provides profiles of telecentre usage and discusses the potential and challenges of setting up and maintaining community telecentres in the context of poor information infrastructure and limited human capacity.